Exploring the Relationship between Social Surrogate Use and Interpersonal Stress - Chen, Yueping (Transactions on Social Science, Education and Humanities Research, 2023)
In previous studies, we found a positive association between depressive symptoms and social surrogate use that cannot be accounted for by increased loneliness or rejection sensitivity. We think that there might be a third common factor-interpersonal stress. Those who have recently experienced interpersonal stress may develop depressive symptoms and also engage in social surrogate use as a means of self-enhancement. Our project collected data from 190 people via a questionnaire that comprises four different psychological scales. The data shows that the positive correlation between interpersonal stress and social surrogate use frequency was significant. And the relationship between ERS and social surrogate use satisfaction was also significant. The results revealed that interpersonal stress might cause more social surrogate use, and the motivation behind it may be self-enhancement.